INTERNALISASI NILAI TAUHID DALAM PEMBELAJARAN SAINS - Darmana, Ayi (Jurnal Pendidikan Islam, 2016)
The study on hypothesis model of internalizing tawheed values in science materials (facts, concepts, and law) is expected to increase relative constribution of learning science toward achieving the national education objectives. The internalization will not lessen the scientifics itself. As a media to develop cognitive potency, science could develop the affective one as well. Through the materials, science internalizes the belief regarding all things in this world: things Allah has created, This belief could lead us to the obidience, characteristics and regularity of those things God created (Sunatullah), so that people can learn from them. It would enable the development of positive attitude, admiration to God’s power and love, gatitude and loyalty to Him. The internalization of tawheed values in science materials can be done through the discussion on the value/moral lesson/nature of the material from Islam perspective.